2022
DOI: 10.1007/s41465-022-00255-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Theta and Beta Neurofeedback Training Protocols on Cognitive Control in ADHD

Abstract: Neurofeedback (NF) is an important treatment for attention deficit/hyperactivity disorder (ADHD). In ADHD, cognitive control deficits pose considerable problems to patients. However, NF protocols are not yet optimized to enhance cognitive control alongside with clinical symptoms, partly because they are not driven by basic cognitive neuroscience. In this study, we evaluated different EEG theta and/or beta frequency band NF protocols designed to enhance cognitive control. Participants were n = 157 children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…In 8 out of 10 studies, theta waves decreased following the intervention. Three studies reported an increase in beta waves [25,46,47], two showed no difference [27,52], and one indicated a decrease [34]. Of the six studies measuring alpha waves, four reported increase [27,33,34,47], while of the six studies measuring theta/beta ratio, three reported decrease [25,38,47].…”
Section: Adaptive Patternsmentioning
confidence: 99%
“…In 8 out of 10 studies, theta waves decreased following the intervention. Three studies reported an increase in beta waves [25,46,47], two showed no difference [27,52], and one indicated a decrease [34]. Of the six studies measuring alpha waves, four reported increase [27,33,34,47], while of the six studies measuring theta/beta ratio, three reported decrease [25,38,47].…”
Section: Adaptive Patternsmentioning
confidence: 99%
“…Theta/beta NFB, considered the gold standard of NFB, trains patients to decrease activity in the theta (θ) frequency band and concomitantly increase activity in the beta (β) frequency band (ie, a θ↓β↑ protocol) to improve cognitive control deficits. 17 Beta and theta band fluctuations have been associated with memory and attention. 18…”
Section: Introductionmentioning
confidence: 99%
“…Theta/beta NFB, considered the gold standard of NFB, trains patients to decrease activity in the theta (θ) frequency band and concomitantly increase activity in the beta (β) frequency band (ie, a θ↓β↑ protocol) to improve cognitive control deficits. 17 Beta and theta band fluctuations have been associated with memory and attention. 18 A previous study introduced the technique of low-resolution electromagnetic tomography analysis (LORETA) Z-score NFB (LZNFB); this technique involves a greater number of electrodes (19-channel scalp sensors) during treatment and achieves faster effective results than conventional surface NFB.…”
Section: Introductionmentioning
confidence: 99%